2008
DOI: 10.4161/cc.7.5.5402
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation mediates Sp1 coupled activities of proteolytic processing, desumoylation and degradation

Abstract: Cell signaling pathways induce Sp1 phosphorylation, which allows for the upregulation of Sp1-dependent genes that control cell growth, cell cycle progression, survival and tumorigenesis. Sp1 activity is under constitutive repression through the sumoylation of Lysine-16, and Lysine-16 dependent N-terminal cleavage relieves this repression. The present investigation probes further into the mechanisms of Sp1 processing, desumoylation and degradation to reveal that phosphorylation is the major driving force behind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 30 publications
2
36
1
Order By: Relevance
“…It will be now of great importance to determine if the Sp proteins, besides controlling basal gene expression, play also a pivotal role in the molecular mechanism(s) involved in the transcriptional regulation of the UbC promoter. Since several reports described the implications of ubiquitin-dependent proteolytic processing in controlling both the level and the transactivation potential of Sp1 (Spengler et al, 2008;Wang et al, 2008), our findings raised the intriguing hypothesis that Sp1-mediated expression of the ubiquitin substrate could, in turn, regulate the level of the transcription factor, thus establishing a regulatory loop to fine-tune UbC gene activity. In addition, we recently demonstrated that fluctuations in intracellular ubiquitin content may actively modulate the level of the regulatory protein p53 (Crinelli et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…It will be now of great importance to determine if the Sp proteins, besides controlling basal gene expression, play also a pivotal role in the molecular mechanism(s) involved in the transcriptional regulation of the UbC promoter. Since several reports described the implications of ubiquitin-dependent proteolytic processing in controlling both the level and the transactivation potential of Sp1 (Spengler et al, 2008;Wang et al, 2008), our findings raised the intriguing hypothesis that Sp1-mediated expression of the ubiquitin substrate could, in turn, regulate the level of the transcription factor, thus establishing a regulatory loop to fine-tune UbC gene activity. In addition, we recently demonstrated that fluctuations in intracellular ubiquitin content may actively modulate the level of the regulatory protein p53 (Crinelli et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Studies of multiple sequence-specific transcription factors indicate that phosphorylation of residues in the vicinity of SUMOylation sites can alter SUMOylation (17,29,37,59,63,66,67). Thus, a subset of SUMOylation motifs in factors such as HSFs (29) and ERR ␣ and ␥ (63, 67) conform to the recently described phosphorylation-dependent SUMOylation In this regard, phosphorylation may provide an additional negative charge, which appears to favor SUMOylation in certain contexts (72).…”
Section: Discussionmentioning
confidence: 99%
“…An interesting hypothesis is that Sp3 phosphorylation by ERK1/2 favors other post-translational modifi cations, such as acetylation or sumoylation, which can also be responsible for Sp3-mediated repression. Indeed, it has been reported that sumoylation and ubiquitination of Sp1 transcription factor can be mediated by phosphorylation ( 48 ), supporting a novel mechanism of Sp-dependent gene regulation. This is also a feature of the ERK1/2 MAPK family to control transcriptional regulation as players between phosphorylation-dependent post-translational modifi cations that can affect protein's transcriptional activity from ubiquitination to sumoylation and acetylation ( 49 ).…”
Section: Downloaded Frommentioning
confidence: 99%